2023
DOI: 10.1186/s13098-023-01092-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety evaluation of SGLT2i on blood pressure control in patients with type 2 diabetes and hypertension: a new meta-analysis

Abstract: Background The clinical efficacy and safety of SGLT2i in treating patients with type 2 diabetes mellitus and hypertension lack immense data support. Objective To systematically evaluate the clinical efficacy and safety of SGLT2i in patients with type 2 diabetes mellitus and hypertension by collecting the previously published randomized controlled trials on SGLT2i to provide data support for SGLT2i as an adjuvant in the first-line antihypertensive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…SGLT2 inhibitors have shown blood pressure-lowering effects [19]. We did not find significant changes of blood pressure, which was measured as office blood pressure and not the primary focus of the study.…”
Section: Discussionmentioning
confidence: 54%
“…SGLT2 inhibitors have shown blood pressure-lowering effects [19]. We did not find significant changes of blood pressure, which was measured as office blood pressure and not the primary focus of the study.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, a new meta-analysis reported that SGLT2 inhibitors should be explored as an adjuvant medication for first-line antihypertensive treatment in individuals with T2D and hypertension who have a low risk of genital infection. 23…”
Section: Resultsmentioning
confidence: 99%
“…Instead, it travels through the nephron, is excreted through the urine, and subsequently decreases blood sugar. Recent research revealed that in addition to reducing blood sugar, SGLT2i also decreases blood pressure in diabetic hypertensive individuals [31]. The mechanism by which blood pressure is decreased is not entirely understood, but it is possible that osmotic and natriuretic diuresis decreases circulating plasma volume eventually leading to decreased blood pressure [32,33].…”
Section: Sglt2 and Diabetesmentioning
confidence: 99%